Biospeckle‐characterization of hairy root cultures using laser speckle photometry. Issue 7 (2nd June 2020) - Schott, Carolin; Steingroewer, Juliane; Bley, Thomas; Cikalova, Ulana; Bendjus, Beatrice
Abstract: Monitoring is indispensable for the optimization and simulation of biotechnological processes. Hairy roots (hr, plant tissue cultures) are producers of valuable relevant secondary metabolites. The genetically stable cultures are characterized by a rapid filamentous growth, making monitoring difficult with standard methods. This article focuses on the application of laser speckle photometry (LSP) as an innovative, non‐invasive method to characterize Beta vulgaris (hr). LSP is based on the analysis of time‐resolved interference patterns. Speckle interference patterns of a biological object, known as biospeckles, are characterized by a dynamic behavior that is induced by physical and biological phenomena related to the object. Speckle contrast, a means of measuring the dynamic behavior of biospeckles, was used to assess the biospeckle activity. The biospeckle activity corresponds to processes modifying the object and correlates with the biomass growth. Furthermore, the stage of the cultures' physiological development was assessed by speckle contrast due to the differentiation between active and low active behavior. This method is a new means of monitoring and evaluating the biomass growth of filamentous cultures in real time. As a potential tool to characterize hairy roots, LSP is non‐invasive, time‐saving, can be used online and stands out for its simple, low‐cost setup.